Reduction of vicinal diketones by yeast in dependence of carbon dioxide pressure - Šepeľová, Gabriela; Cvengroschová, Mariana; Šmogrovičová, Daniela (BrewingScience, 2003)
One of the possibilities how to make beer production more effective is lowering the time of diacetyl and 2,3-pentanedione reduction. These compounds, collectively referred as vicinal diketones, are very important since their taste limits are very low and evolve undesirable change of beer flavour, which is known as buttery, cottage cheese or whey taste. The aim of our work was to study an influence of carbon dioxide pressure during the active carbohydrate fermentation and the end of fermentation on vicinal diketones reduction. We compared vicinal diketones reduction in young beers fermented under carbon dioxide pressure of 100 kPa during the whole main fermentation and in beers fermented without carbon dioxide pressure until extract concentration decreased to 7.5 °P and then under carbon dioxide pressure of 50 kPa. Experiments were done in the wort fermentation of gravity 12.5 °P and 13.5 °P. Lower carbon dioxide pressure accelerated vicinal diketones reduction and speeded up the end of fermentation. Wort concentration had no influence on vicinal diketones reduction in studied wort gravities (12.5 °P and 13.5 °P).